(untitled) (Fiep Bulletin - online, 2015)
Article I The International Federation D'Education Physique (FIEP) founded in 1923 in Brussels, has as its aim to favour the development of education, physical and keeping fit activities, in all countries and to contribute to international cooperation in this domain